Implementing a colostrum-kit reduces the time to first colostrum for neonates admitted to the NICU – a retrospective observational study - Sara Hellström; Karolina Linden; Verena Sengpiel; Anders Elfvin (International Breastfeeding Journal)
Abstract Background The World Health Organisation states that newborns should receive colostrum as soon as possible after birth. However, among newborns needing neonatal intensive care, initiation of lactation and access to colostrum might be delayed. At the centre of this study, a tertiary care hospital in Sweden (10,000 deliveries/year), few admitted infants received colostrum within the day of birth, warranting a quality improvement. In order to reduce the time from birth to first colostrum received by infants admitted to the Neonatal Intensive Care Unit (NICU), a new clinical routine including a colostrum-kit, was implemented as standard care in June 2018. The colostrum-kit contained information about hand expression of breastmilk as well as material for collecting, labelling and transporting the colostrum. The kit should be handed to all birthing parents with infants admitted to the NICU. Methods Data on time in minutes from birth to first colostrum administered to the infant (oral mouth care, oral feeding or gavage feeding) was retrieved for all infants born between 1 September 2016 and 31 October 2023, admitted to the NICU within 1h from birth. Infants were divided into four time-cohorts, compared with nonparametric ANOVA. Results The study included 3618 infants born at 22 + 0 – 43 + 0 weeks gestational age, of whom 2814 (78%) had available data on time to colostrum. Median (IQR) time in hours was 35 (20–36) pre-implementations, followed by 18 (7–38), 11 (4–26) and 8 (3–22) in the subsequent follow-up cohorts, p < 0.001. Subgroups of mode of delivery had median (IQR) pre-implementation of 30 (19–54) for vaginal and 47 (23–72) for caesarean section that reached 7 (2–18) and 9 (3–26) in the last follow-up. Subgroups of gestational age (< 28, 28–31, 32–36, > 36 weeks) had a pre-implementation time of 48 (26–80), 46 (23–73), 33 (20–60) and 32 (19–57), that in the last follow-up was reduced to 4 (2–20), 7 (2–29), 9 (2–33) and 9 (4–19). Conclusions Implementing a colostrum-kit for infants admitted to the NICU significantly reduced the time to first colostrum administered to the infant in all gestational ages. The difference between subgroups of gestational age or mode of delivery was reduced. The effect persisted over time.